Dynamic Characteristics of the Surrounding Soil during the Vibrational Pulling Process of a Pile Based on DEM - Tingting Sun; Zhihua Zhang; Jixin Yang; Jingnan Yang; Xuan Zhang (Shock and Vibration)
When bridge construction has been completed, the temporary support system, such as a steel-pipe pile, is dismantled, and problems that are related to the steel-pipe piles pulling from the strata are encountered. It is difficult to measure the dynamic characteristics of the surroundings during the deep pile-pulling process. A numerical model of the pulling pile is established by using the discrete element method (DEM). A sinusoidal dynamic load is executed on the pile with various vibrational frequencies. The stress, bond, coordination number, porosity, and velocity field distribution of the surrounding soil during the pile-pulling process are studied. The results demonstrate that, during the pile-pulling process, the shearing state of the surrounding soil depends on the position of the pile. The number and area of bond fractures gradually increase, the coordination number decreases, and the porosity gradually increases when the pile-pulling distance increases. Under a vibrational load, the area that corresponds to particles with large velocity and displacement expands with the increase of the vibrational frequency. The major influence zone of the pile pulling on both sides is concentrated within 6dpile, which can be used to evaluate the safety of the existing bridge nearby during pile pulling.